Assessment of the stability of drugs in the amorphous and co-amorphous form in extrudates, pellets and tablets designed to circumvent drugs’ poor water solubility - Costa, Nuno Gonçalo Ferreira da (2022)
The synthesis of innovative drug substances has been seriously compromising the development of oral drug products with satisfactory bioavailability properties. Amorphization and co-amorphization of drugs have been described as promising strategies to enhance the bioavailability of poorly water-soluble drugs. Olanzapine (OLZ), an atypical antipsychotic drug used for the treatment of schizophrenia or bipolar disorder, was used as model drug due to its poor aqueous solubility and insufficient bioavailability. The solubility of the drug was enhanced by amorphization and co-amorphization with sulfonic acids. Among the sulfonic acids used to stabilize OLZ in the amorphous form (>6 months, at 25°C/75% relative humidity), saccharin yielded the co-amorphous system with the highest solubility and dissolution rate (145-fold and 4-fold enhancement compared to its crystalline counterpart, respectively), thus supporting its utilization in the manufacture of oral drug products. Tableting of powdered mixtures containing co-amorphous OLZ resulted in compacts with no evidence ofrecrystallization of the drug, regardless of the compression pressure imposed. These compacts presented high tensile strength and disintegration times, and thus, a fine-tuning of the formulation was conducted to ensure the rapid release of the drug. Unfortunately, the high cohesiveness and poor flowability of co-amorphous OLZ requires additional processing steps to enhance the flowability and guarantee the production of drug products with the desired quality. Consequently, wet granulation was considered through the application of different fractions of solvent and drying temperatures to materials. Whilst amorphous OLZ recrystallized back to its crystalline counterpart (form I) during processing, co-amorphous OLZ was stable to the stress conditions imposed to materials and, therefore, enabled the manufacture of drug products containing the highly soluble amorphous form. Overall, the work highlighted the stability of co-amorphous OLZ during the manufacture of oral drug products suggesting a higher bioavailability.